Central hemodynamics in ultra-endurance athletes - Knez, W. L.; Sharman, J. E.; Jenkins, D. G.; Coombes, J. S. (Journal of Science and Medicine in Sport, 2008)
Central hemodynamics such as ascending aortic blood pressure (BP), wave reflection and myocardial perfusion are clinically important in the context of cardiovascular health. Ultra-endurance athletes may be at greater risk of cardiovascular abnormalities due to chronically increased physiological stress placed on the cardiovascular system. This study was a cross-sectional investigation that compared central hemodynamics in ultra-endurance athletes and matched controls. Forty-four athletes (36 males; aged mean ± S.D., 34 ± 8 years) undergoing ultra-endurance training (16.3 ± 3.7 h/week) were compared to 44 matched recreationally active (1.2 ± 0.9 h/week) controls (36 males; aged 34 ± 8 years). Brachial BP was measured using an oscillometric device while central hemodynamics including ascending aortic BP, wave reflection (augmentation index, AIx), ejection duration, sub-endocardial perfusion (SEVR) and timing of the reflected wave (TR) were determined by applanation tonometry and pulse wave analysis. There were no significant (P > 0.05) differences between groups in AIx (athletes and controls; 6 ± 12% versus 6 ± 13%, respectively), TR (athletes and controls; 165 ± 22 ms versus 165 ± 19 ms, respectively), brachial (athletes and controls; 51 ± 9 mmHg versus 48 ± 12 mmHg, respectively) or central pulse pressure (33 ± 5 mmHg versus 31 ± 7 mmHg). However, athletes had significantly increased SEVR (226 ± 42% versus 198 ± 46%; P < 0.001) despite having a longer ejection duration (348 ± 19 ms versus 339 ± 18 ms; P < 0.05). Furthermore, the amount of exercise training volume was significantly related to central (r = -0.46; P = 0.002), but not brachial pulse pressure (r = -0.28; P > 0.05). Ultra-endurance athletes had increased sub-endocardial perfusion capacity and the quantity of exercise training was associated with central rather than peripheral hemodynamics.